2016
DOI: 10.1589/jpts.28.1738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exhalation exercise on trunk muscle activity and oswestry disability index of patients with chronic low back pain

Abstract: [Purpose] This study investigated the effect of exhalation exercises on trunk muscle activity and Oswestry Disability Index by inducing trunk muscle activity through increasing intra-abdominal pressure and activating muscles, contributing to spinal stability. [Subjects and Methods] This intervention program included 20 male patients with chronic low back pain. A total of 10 subjects each were randomly assigned to an exhalation exercise group as the experimental group and a spinal stabilization exercise group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The reason for this is that a decreasing sacral angle increases stability while decreasing mobility but improves stability and mobility at the same time through the pelvic movement. This result improves the stability of the sacroiliac joint and the physiological effects of the areas surrounding the lumbar disc 20 ) since it results in functional improvement of the back by reducing stress on the spine and sacroiliac joint 16 ) . Thus, this study demonstrated that the balance center stabilization resistance exercise, which increases sacroiliac joint stability by controlling balance through pelvic movements, can be clinically effective in patients with lumbar disc herniation causing postural and spinal imbalances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is that a decreasing sacral angle increases stability while decreasing mobility but improves stability and mobility at the same time through the pelvic movement. This result improves the stability of the sacroiliac joint and the physiological effects of the areas surrounding the lumbar disc 20 ) since it results in functional improvement of the back by reducing stress on the spine and sacroiliac joint 16 ) . Thus, this study demonstrated that the balance center stabilization resistance exercise, which increases sacroiliac joint stability by controlling balance through pelvic movements, can be clinically effective in patients with lumbar disc herniation causing postural and spinal imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of the Korean version of the back pain disability index is high (r=0.92). The back pain disability index is evaluated as maximum 45 points; the higher the total score, the greater the degree of disability and the lower the functional performance 15 , 16 ) .…”
Section: Methodsmentioning
confidence: 99%
“…With the lower back and pelvis aligned, a pressure biofeedback device (Stabilizer™, Pressure Biofeedback Unit, USA) is placed on the lower back, and the pressure is set to 40 mmHg. The participant forcefully contracts his/her abdominal muscles to increase the pressure to 70 mmHg and holds the contraction (Kang et al 2016, Lee et al 2018a).…”
Section: Abdominal Hollowingmentioning
confidence: 99%
“…83,84 This method of breathing allows for the relaxation of lumbar muscles and an improvement in pelvic mobility, and may effectively relieve and prevent back pain. 85 When trained properly, the surgeon should feel empowered to practice all these exercises routinely to improve mobility, enhance flexibility, and, ultimately, decrease pain.…”
Section: Prevention Through Conditioningmentioning
confidence: 99%